2016
DOI: 10.1111/nmo.12773
|View full text |Cite
|
Sign up to set email alerts
|

Gastric ghrelin, GOAT, leptin, and leptinR expression as well as peripheral serotonin are dysregulated in humans with obesity

Abstract: Our data indicate that obesity causes a dysregulation of gastrointestinal hormones at the tissue level and serum, including a negative correlation with an increased marker of subclinical inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
7
10
1
Order By: Relevance
“…An increased number of ghrelin positive cells has previously been reported in the gastric corpus of obese patients . We only observed an increase in ghrelin tissue content in the antrum of obese patients.…”
Section: Discussionsupporting
confidence: 48%
“…An increased number of ghrelin positive cells has previously been reported in the gastric corpus of obese patients . We only observed an increase in ghrelin tissue content in the antrum of obese patients.…”
Section: Discussionsupporting
confidence: 48%
“…This is accompanied by ghrelin resistance in neural circuits that regulate energy homeostasis, which protects the body from a higher body weight set-point during excessive food availability (38). Contradictory findings have been reported on the effect of obesity on ghrelin mRNA expression, or the number of ghrelin-positive cells in biopsies (39)(40)(41)(42). Our study in primary fundic cultures from whole stomach samples from multiorgan donors and obese patients undergoing bariatric surgery provide a more elegant model to study the mechanisms involved.…”
Section: Discussionmentioning
confidence: 74%
“…Work by Hernandez et al (2012) demonstrated that administration of a HFD to lactating rats increased the mRNA expression of Tph1 in the mammary gland, along with elevated levels of inflammatory marker Tnfa [22]. Finally, obese patients have demonstrated reduced circulating serotonin concentrations relative to non-obese patients, potentially resulting in reduced lipolysis and increased lipid storage [23]. Additionally, numerous pharmacotherapies used in the treatment of obesity manipulate both the central and peripheral serotonin systems [24].…”
Section: Introductionmentioning
confidence: 99%